Facilitated anion transfer reactions across oil∣water interfaces - Dassie, Sergio Alberto (2010)
In this paper we present the general equations for a model of anion transfer reactions across the oildivideswater interface assisted by a neutral ligand. Our analysis mainly focuses on the effect of water autoprotolysis. The equations reported here allow us to simulate the system under a variety of possible conditions. The formation of complex with j:k anion-to-ligand stoichiometry is analyzed. Three different models are compared: buffered solutions (BASA model) and unbuffered solutions with and without considering water autoprotolysis (UBASA and UBAS model respectively). Moreover, the analytical relationships for the BASA model between half-wave potential and the initial concentration of anion and ligand are developed. © 2010 Elsevier B.V. All rights reserved.